Yield of sweet corn in response to fertilizer sources - H.A, Akintoye (Global Journal of Food and Agribusiness Management, 2022)
Alternative source of plant nutrition is now becoming imperative in vegetable production in Nigeria, because of health problems associated with excessive usage of inorganic fertilizer. Research was conducted in vegetable research plot of National Horticultural Research Institute (NIHORT), Ibadan, Nigeria, to evaluate the effect of N fertilizer sources and rate on the growth and development of sweet corn. Fertilizer sources significantly increased yield and its components at both years of study. Sweet corn yields with applied inorganic were greater than those receiving organic sources of fertilizer. Sweet corn yielded 3063 kg ha-1 and 3333 kg ha-1 in 2003 and 2004 at 120 kg ha-1 inorganic fertilizer rate compared to 1803 kg ha-1 and 996 kg ha-1 in 2003 and 2004 respectively, with organomineral fertilization. These results suggest that sweet corn yield could be enhanced by the application of inorganic fertilizer, because of the slow release nature of organic sources of fertilizer in relation to growth duration.